Reducing Escherichia coli O157:H7 in agriculture: interventions for cattle and romaine lettuce - Maher, Joshua Martin (Kansas State University, 2020)
The foodborne pathogen Escherichia coli O157:H7 represents a significant public health threat, with cattle representing the primary reservoir for this bacteria. Outbreaks of E. coli O157:H7 in beef carry a storied past; however, recently romaine lettuce has also been implicated in numerous outbreaks in the United States, sickening hundreds and dramatically altering consumer’s perspective on the safety of this commodity. This dissertation focuses on novel interventions for the control of E. coli O157:H7 in agriculture, emphasizing cattle and fresh-cut romaine lettuce. The first pre-harvest food safety intervention evaluated the administration of Megasphaera elsdenii (ME)—a lactic acid-utilizing probiotic—and monitored the influence on E. coli O157:H7 shedding in cattle. Inclusion of ME in cattle finishing diets did not reduce the prevalence of E. coli O157:H7 compared to cattle fed control diets (P=0.5012), yet the ME x time interaction was significant (P=0.0323), indicating prevalence varied based upon dose and sampling period. ME reduced the odds of E. coli O157:H7 prevalence by 50% during sampling period 1 (P=0.0921) and increased the odds by 23% during sampling period 2 (P=0.6130). A similar pre-harvest food safety study included Enogen Feed Corn® (EFC)—which features a genetically enhanced α-amylase enzyme trait—fed as steam-flaked corn and silage to investigate the potential impact on E. coli O157:H7 shedding in cattle. A 43.3% reduction in the odds of E. coli O157:H7 prevalence in cattle fed diets containing EFC versus a control corn diet was observed, with possible mechanisms for this reduction requiring further investigation. Finally, the need for effective postharvest produce wash interventions for the control of E. coli O157:H7 in fresh-cut romaine lettuce was addressed, with a twofold purpose: 1) assessment of sodium bisulfate (SBS) and peroxyacetic acid (PAA) effect on produce quality compared to chlorine, water, and unwashed control treatments, and 2) evaluation of potential E. coli O157:H7 reductions using a blend of SBS and PAA as a postharvest wash intervention. Quality data—including overall visual quality, browning and discoloration, phytotoxicity, and color analyses—indicated all treatments were acceptable for fresh-cut romaine lettuce, with these data informing treatment concentration selection in the subsequent inoculation study. When applied to inoculated product, all treatments achieved significant reductions of E. coli O157:H7 in comparison to the unwashed control. SBS+PAA produced the greatest reduction (2.3 CFU/g), followed by SBS (2.2 CFU/g), and PAA (1.9 CFU/g); however, these reductions were statistically similar to one another (P>0.05). Following the scientific presentation of each food safety technology (probiotics, genetically enhanced animal feed, and postharvest wash water interventions), approval considerations were provided with respect to the United States (U.S.) and European Union (EU) regulatory frameworks. Careful analysis of the similarities and differences between U.S. and EU policy was provided, addressing: 1) regulatory definitions, 2) the approval process, and 3) risk assessment vs. the precautionary principle. This dissertation celebrates the promise of novel food safety technologies for the control of E. coli O157:H7 in agriculture, while capturing the scientific, regulatory, and approval-related issues surrounding them.
Keywords: Food safety; Escherichia coli; Intervention; Feedlot cattle; Fresh-cut romaine lettuce; Food policy